ETIKA NOTARIS: KEPRIBADIAN, PELAYANAN, TUGAS, WEWENANG, DAN PENEGAKAN KODE ETIK - Ma’ruf Amin; Jauharotun Nakiyah; Nabilah Roihanah Ramadhani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article will outline and summarize the code of ethics of the Notary profession based on the code of ethics law that has been established, the Code of Ethics is the moral principles inherent in a profession and are compiled systematically. A professional code of ethics is a norm set and agreed upon by a professional group, which directs or instructs its members on how to act, and at the same time ensures that the profession is viewed morally by society. Not all professions will adhere to the same principles. The code of ethics serves to control society and prevent interference from other parties, prevent misunderstandings and conflicts, and ensure that members of professional groups fulfill their obligations. The goal is to maintain the dignity of the profession, maintain and maintain the welfare of members, improve member service, improve the quality of the profession and the organization, improve services, strengthen the organization, avoid unfair competition, establish close relationships with members, and set standards. Important for law enforcement are the principles of humanity, justice, propriety, honesty, and the implementation of the code of ethics.